2011
DOI: 10.3390/genes2030449
|View full text |Cite|
|
Sign up to set email alerts
|

Reassessing Domain Architecture Evolution of Metazoan Proteins: Major Impact of Gene Prediction Errors

Abstract: In view of the fact that appearance of novel protein domain architectures (DA) is closely associated with biological innovations, there is a growing interest in the genome-scale reconstruction of the evolutionary history of the domain architectures of multidomain proteins. In such analyses, however, it is usually ignored that a significant proportion of Metazoan sequences analyzed is mispredicted and that this may seriously affect the validity of the conclusions. To estimate the contribution of errors in gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 58 publications
(86 reference statements)
3
29
0
Order By: Relevance
“…Domain architecture deviation. Rationale: changes in domain architecture of proteins are relatively rare evolutionary events (whereas the error rate in gene prediction is relatively high); therefore, if we find a hypothetical protein with a ‘novel’ domain architecture, then this is more likely to reflect an error in gene prediction than true innovation (10). (It must be pointed out that MisPred tool 11 is not yet available in searches on the MisPred website and that data generated with this tool are not yet deposited in the MisPred database.…”
Section: Database Generationmentioning
confidence: 99%
“…Domain architecture deviation. Rationale: changes in domain architecture of proteins are relatively rare evolutionary events (whereas the error rate in gene prediction is relatively high); therefore, if we find a hypothetical protein with a ‘novel’ domain architecture, then this is more likely to reflect an error in gene prediction than true innovation (10). (It must be pointed out that MisPred tool 11 is not yet available in searches on the MisPred website and that data generated with this tool are not yet deposited in the MisPred database.…”
Section: Database Generationmentioning
confidence: 99%
“…Moreover, they demonstrated that terminal domain loss seldom involves losing only part of a domain, or rather, that such partial losses quickly progress into loss of the entire domain. However, it is important to ensure such observations are not confounded by cases where errors in gene boundary recognition make domain detection less accurate [73].…”
Section: Domain Mobility Promiscuity or Versatilitymentioning
confidence: 99%
“…A detailed case study was made recently of netrin domaincontaining proteins, where polyphyletic evolution in metazoa seems well-supported [88]; these authors further suggest the term merology for such polyphyletic evolution. A series of papers by Nagy and Patthy et al [73,89,90] further elaborates on challenges faced within this line of research; they report strong confounding influence of gene prediction errors. They further propose the term epaktology for gene similarity resulting from the independent acquisition of two proteins by the same additional domain.…”
Section: Polyphyletic Domain Architecture Evolutionmentioning
confidence: 99%
“…As pointed out in the accompanying paper [4], reliable reconstruction of the evolutionary history of DA of multidomain proteins requires that the protein sequences compared are valid, complete and correct and that the evolutionary relationship of the multidomain proteins compared is correctly defined.…”
Section: Introductionmentioning
confidence: 99%